Using a content management system for shared access to learning resources - D. S. Lazarenko (Academy of Cognitive and Natural Sciences, 2013)
One of the areas of development of the World Wide Web that requires complex scientific research is data and content management. This industry contains such areas as big data management, cloud-based data management, multimedia data management, and is also involved in Web-mining, the tasks of clustering, classification and analysis of data in the Web, Web content modeling, Semantic Web, etc. The task of effective Web content management has become very important for many industries that have emerged on the basis of the WWW infrastructure, including Internet commerce, distance learning and educational Web resources, managing large information portals, developing and maintaining corporate portals, creating Web-resources electronic management, supporting personal sites and blogs.